"Nivel de satisfacción percibida por el usuario hospitalizado y calidad de atención de Enfermería - Hospital Regional Docente de Trujillo, 2008" - Muñoz Pino, Adinda (2008)
This research is a descriptive correlational cross, was conducted in patients hospitalized for surgery service "B" Regional Teaching Hospital Trujillo, 2008. The population sample consisted of a total of 120 hospitalized users, who were elected by simple random sampling; we applied a survey, with the purpose of determining the relationship between quality of nursing care and the level of satisfaction felt by the User hospitalized. The data collected were processed using a pattern and statistical manual tabulation through the test of independence of criteria (chi-square), the results were arrived at the following conclusions: 1. 60.8 percent of users receive a quality hospital care nursing optimal, the 31.7 percent receive quality care and only half a 7.5 percent receive a lower quality of care. 2. The 58.3 percent of users are hospitalized with a good level of satisfaction for the care provided by nurses, 38.3 of the users have a satisfaction level and half the 3.3 percent low. 3. There is a significant relationship between the quality of nursing care and the level of satisfaction felt by the user hospitalized in the Department of Surgery "B" Regional Teaching Hospital of Trujillo.